MENCIPTAKAN BRANDING DAN MEMBANGUN SALURAN DISTRIBUSI BERDASARKAN PERSEPSI PENGUSAHA (STUDY PADA DISTRIBUTOR PT SINERGI SEJUTA USMIK KOTA SURABAYA) - Permadi, Fahrulrozi Adi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study is to find out the branding and distribution channels that are carried out by PT Sinergi Sejuta Usmik so that the company is increasingly widely known by the Indonesian people. Data collection was done by means of the interview method. With informants, namely the owner and marketing manager who have an important role for the progress of the Company. The results of this study state that the branding carried out by PT Sinergi Sejuta Usmik is still not fully implemented as expected because there are still many things that happen because they have to choose what company to partner with to be part of the branding that is being carried out. With what the Owner and Marketing Manager have done, building distribution channels anywhere can be done as long as it can benefit the company and by building distribution channels not only makes PT Sinergi Sejuta Usmik widely known but can also help marketing MSME actors from throughout Indonesia.